2005
DOI: 10.1021/jp044755u
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Nucleation of Poly(p-phenylene vinylene-co-2,5-dioctyloxy-m-phenylene vinylene) Crystallization by HiPco Single-Walled Carbon Nanotubes

Abstract: Hybrid systems of the conjugated organic polymer poly(p-phenylene vinylene-co-2,5-dioctyloxy-m-phenylene vinylene)(PmPV) and HiPco single-walled carbon nanotubes (SWNTs) are explored using spectroscopic and thermal techniques to determine specific interactions. Vibrational spectroscopy indicates a weak interaction, and this is further elucidated using differential scanning calorimetry (DSC), confocal laser scanning microscopy, temperature-dependent Raman spectroscopy, and temperature-dependent infrared spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
4
13
0
Order By: Relevance
“…3a and b). Fluorescence studies have been shown to aid in the elucidation of the interaction of nanotubes with different molecular species (Keogh et al, 2005;Hedderman et al, 2006). In an earlier study (Casey et al, 2007a) a model derived by Coleman et al (2004) was adapted and employed to assess the degree of interaction between SWCNT and cell culture medium.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…3a and b). Fluorescence studies have been shown to aid in the elucidation of the interaction of nanotubes with different molecular species (Keogh et al, 2005;Hedderman et al, 2006). In an earlier study (Casey et al, 2007a) a model derived by Coleman et al (2004) was adapted and employed to assess the degree of interaction between SWCNT and cell culture medium.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…The obtained crystalline NiTAPc electropolymers are concentrated on these microscopic pieces of the immobilized SWCNTs, further confirming the ability of the SWCNT to induce crystallinity on the NiTAPc electropolymer. Although, it has been widely reported that CNTs are capable of inducing crystallinity on polymeric species [11], [12], [13], [14], [15], [16], [17], [18] and [19], this represents the first report of such observation for an electropolymer and especially for an MPc electropolymer.…”
Section: Fesem Characterization Of the Bppge-swcnt-poly-nitapcmentioning
confidence: 93%
“…One of the many intriguing properties of CNTs is their ability to induce crystallinity on polymers prepared by solution or melt-processing techniques [12], [13], [14], [15], [16], [17], [18] and [19]. To our knowledge, the induction of crystallinity by CNTs on polymers prepared by electrochemical techniques has not been reported, and we are not aware of any such observation for the electropolymerized films of metallophthalocyanine (MPc).…”
Section: Introductionmentioning
confidence: 99%
“…16 We have shown that temperature cycling facilitates a change in isomerization above the glass transition temperature of the polymer, resulting in an increased polymer tube backbone binding. 16 Raman spectroscopy has been demonstrated to be a key technique for the characterization of SWNTs. This is because of the strong resonant enhancement of the RBMs with respect to tube diameters.…”
Section: Introductionmentioning
confidence: 93%